IDENTIFIKASI KESEHATAN KEUANGAN PERUSAHAAN UNLISTED SEBELUM DAN SESUDAH PANDEMI COVID-19 (STUDI KASUS SURVEI KHUSUS PERUSAHAAN SWASTA NON FINANSIAL TAHUN 2021) - Dwiky Rachmat Ramadhan; Yoga Dwi Nugroho; Dita Desriani (JURNAL ILMIAH EDUNOMIKA, 2023)
Sustainable development (SDGs) resulted in 17 development goals with industrial development being one of the goals. The COVID-19 pandemic has had a real impact on various sectors, including the industrial sector and companies, especially unlisted companies. The company's assets and revenues are greatly affected by this pandemic, so it is necessary to identify this impact, especially on the company's finances. Identification through several financial indicators including Current Ratio (CR), Asset Turnover (PA), Debt to Equity Ratio (DTE), Debt to Asset Ratio (DTA), Return of Assets (ROA), Return of Equity (ROE) and Net Profit margins. To see the company's performance in terms of financial health, the Go Public company will be taken as a comparison or benchmark. This performance comparison can be seen using Levene's Test and Independent T-Test. The results showed that in general, there was a decrease in income and assets for unlisted companies, except for companies in the manufacturing sector that were still able to survive and information and communication companies that grew rapidly. On the other hand, large and medium-sized companies have almost the same performance as Go Public companies during this pandemic. However, small-scale companies are able to generate higher returns relative to assets than Go Public companies.